Regulation of Meadow Saffron (Colchicum autumnale L.) in non-intensively managed grasslands - Jung, Linda S.; Justus Liebig University Giessen (My University, 2014)
During the last decades, the toxic grassland species C. autumnale has become an increasing problem in extensively managed semi-natural grasslands of some Central European regions (Briemle, 2006; Winter et al., 2011). Farmers with high population densities of the plant have increasing difficulties to market their hay. As C. autumnale is sensitive to an increased cutting frequency, there is a risk that farmers intensify or abandon management. This would inevitably lead to high losses of biodiversity as semi-natural grasslands are amongst the most species-rich ecosystems in Europe (Pärtel et al., 2005). The same hazard persists when applying traditionally recommended measures to control C. autumnale (Wehsarg 1929; Braungart, 1899). A measure with a potentially acceptable impact on biodiversity is an early cut without additional fertilization, but respective studies (e.g. Wehsarg, 1929; Briemle&Elsässer, 2008) did not consider effects on plant diversity and are contradictive in the best cutting time. Given this background, the main objective of this thesis was to derive management schemes to reduce toxicity in hay from grasslands with high C. autumnale densities with the smallest possible negative impact on the surrounding vegetation and thus plant species richness. We used three approaches: (i) the collection, critical review, and addition of general information on C. autumnale (chapter 5), (ii) the investigation of the temporary nutrient and alkaloid dynamics of C. autumnale (chapter 6), (iii) the study of the effect of different mowing treatments on the population biology of C. autumnale and plant species diversity (chapter 7). The literature review revealed some contradictive information and information gaps about C. autumnale. We clarified ambiguities with emphasis on C. autumnale morphology. We filled information gaps with our data on the population biology of C. autumnale, distribution range, germination requirements, and seed bank classification.Nutrient and alkaloid dynamics showed a clear dependence on climatic conditions. In the populations located in the cooler biogeographical region, the ratio of the maximum nutrient content between above-ground plant parts and storage organs, as well as alkaloid content in leaves and capsules occurred significantly later. The ratio between the nutrient content in above-ground plant parts and the storage organ peaked at the end of April/beginning of May, at about 25 cm leaf length of C. autumnale. At this developmental stage, a cut removes most nutrients from the plant and leaves it with few storage compounds in the corm. Compared to the common first mowing date (15 June), alkaloid content decreased significantly until 5 July in both study regions. It was about twice higher in plants from the colder region to those in the warmer one.Mowing experiments showed a significant decrease of the population growth rate (Lambda) and the number of large vegetative plants developing capsules in the following year for plots cut in late April/early and late May compared to plots cut in June (control). Repeated flower removal in autumn had no effect on Lamda. Differences in the population growth rates between each treatment and the control were mainly the result of a reduction in growth and survival and an increasing retrogression as shown by LTRE. A cut in late April/early May resulted in the lowest survival probability. Differences in vegetation composition between treatments and the control were detected for the treatment early plus late May cut . After three years of early cutting, no reduction in plant species diversity was observed for any treatment.In summary, results of our studies suggest the following two management options to reduce toxicity in hay from grasslands with C. autumnale: option 1) mowing at about 25 cm plant height of C. autumnale (ca. late April/early May) to reduce its population density or option 2) delayed mowing in late June/early July when the plant has turned brown and dry and alkaloid content has declined. For option 1, the second cut should be postponed to July to enable seed shed of plants. Any grassland management decisions to control toxic C. autumnale must be made in close cooperation with nature conservation authorities to consider site characteristics and requirements of endangered species.

In den letzten Jahrzehnten wird die giftige C. autumnale in einigen Regionen Mitteleuropas auf extensiv bewirtschafteten halbnatürlichen Grünlandflächen zunehmend als problematisch betrachtet (Briemle, 2006; Winter et al., 2011). Bei hohen Populationsdichten haben Landwirte vermehrt Heuvermarktungsprobleme. Da C. autumnale sensibel auf erhöhte Schnittfrequenzen reagiert, besteht die Gefahr der Bewirtschaftungsintensivierung oder -aufgabe betroffener Flächen. Dies würde zu hohen Biodiversitätsverlusten führen, da halbnatürliches Grünland zu den artenreichsten Ökosystemen in Europa zählt (Pärtel et al., 2005). Dieselbe Gefahr besteht bei traditionellen Bekämpfungsmaßnahmen (Wehsarg 1929; Braungart, 1899). Die einzige Maßnahme mit potentiell akzeptabler Wirkung auf die Artenvielfalt ist ein früher Schnitt ohne zusätzliche Düngung, aber betreffende Studien (z. B. Wehsarg, 1929; Briemle&Elsässer, 2008) geben keine Auskunft über die Auswirkung auf die Pflanzenartenvielfalt und widersprechen sich im empfohlenen Schnittzeitpunkt.Vor diesem Hintergrund war das vorrangige Ziel dieser Doktorarbeit, Bewirtschaftungsmaßnahmen für einen reduzierten Giftgehalt in Heu von Grünlandflächen mit hohem C. autumnale Besatz abzuleiten. Der negative Einfluss auf die Begleitvegetation sollte dabei so gering wie möglich sein. Es wurden drei Ansätze genutzt: (i) Sammlung, kritische Bewertung und Ergänzung von Informationen zu C. autumnale (Kapitel 5), Untersuchung (ii) der zeitlichen Veränderung von Nährstoff- und Alkaloidgehalten (Kapitel 6) und (iii) Evaluierung des Einflusses verschiedener Mahdregime auf C. autumnale und die Pflanzenartenvielfalt (Kapitel 7).Die Literaturauswertung zeigte Widersprüche und Informationslücken zu C. autumnale. Wir klärten v. a. morphologische Zweideutigkeiten, z. B. Ursprung, Funktion und Definition bestimmter Organe. Wir füllten Informationslücken mit eigenen Daten zu Populationsbiologie, Verbreitung, Keimungsansprüchen und Samenbankklassifizierung.Der zeitliche Verlauf der Nährstoff- und Alkaloidgehalte in C. autumnale zeigte eine klimatische Abhängigkeit und war im kälteren Naturraum verzögert. Der Quotient aus den Nährstoffgehalten der über- und unterirdischen Pflanzenteile erreichte sein Maximum Ende April/Anfang Mai bei etwa 25 cm Blattlänge von C. autumnale. In diesem Stadium werden der Pflanze durch Schnitt die meisten Nährstoffe entzogen - bei nur geringen Mengen an Reservestoffen in der Knolle. Verglichen mit dem üblichen ersten Schnitttermin (15. Juni), nahm der Alkaloidgehalt in beiden Untersuchungsregionen signifikant zum 5. Juli ab. Er lag bei den Pflanzen im kühleren Naturraum etwa doppelt so hoch wie bei denen im wärmeren. Die Mahdexperimente zeigten eine signifikante Abnahme der Populationswachstumsrate (Lambda) und Reproduktionsrate bei einem Schnitt Anfang oder Ende Mai verglichen mit einem Junischnitt (Kontrolle). Eine wiederholte Blütenentfernung im Herbst hatte keinen Effekt auf Lambda. Unterschiede in Lambda zwischen Behandlungen und Kontrolle lagen laut LTRE v. a. in einer Reduktion der Wachstums-, Überlebensrate und Pflanzengröße begründet. Die geringste Überlebenswahrscheinlichkeit zeigte sich bei einem frühen Schnitt Ende April/Anfang Mai. Unterschiede in der Vegetationszusammensetzung zwischen Behandlungen und Kontrolle wurden nur für die Variante früher plus später Maischnitt verzeichnet. Auswirkungen auf die Pflanzenartenvielfalt wurden nicht festgestellt. Zusammenfassend lassen sich folgende zwei Bewirtschaftungsempfehlungen ableiten, um den Giftgehalt in Heu von Grünland mit C. autumnale zu reduzieren: Option 1) Mahd von C. autumnale bei 25 cm Größe (ca. Ende April/Anfang Mai) zur Reduktion der Populationsdichte; Option 2) Verschiebung des Mahdtermins auf Ende Juni/Anfang Juli, wenn die Pflanze braun und vertrocknet ist und der Alkaloidgehalt reduziert. Bei Option 1 sollte der zweite Schnitt auf Juli verschoben werden, um ein Aussamen der Begleitvegetation zu ermöglichen. Bewirtschaftungsentscheidungen zur Kontrolle der giftigen C. autumnale müssen in enger Zusammenarbeit mit Naturschutzbehörden erfolgen, um Standorteigenheiten und Ansprüche gefährdeter Arten zu berücksichtigen.
Regulation der Herbst-Zeitlose (Colchicum autumnale L.) in extensiv bewirtschaftetem Grünland
Keywords: Management; Bewirtschaftung; Bekämpfung; Giftpflanze; Colchicin; management; control; toxic weed; colchicine; ddc:630